ALGORITHM FOR OPTIMAL RESERVATION OF DISTRIBUTED COMPUTING RESOURCES BASED ON THE CRITERION OF EFFICIENT USE OF COMPUTING NODES - Ilyashenko М. B. (Radio Electronics, Computer Science, Control, 2024)
This paper presents algorithm for optimal distributed resources reservation, that allow to find reservation areas according to minimal amount of used computational nodes optimization criteria and maximal productivity usage of equipped computational nodes criteria. Paper contains detailed algorithm description, including set of preliminary conditions that reduce computational complexity of enumerating part of algorithm.